227k views
2 votes
Subtract -5x+7 from 3x-2 set up your expression show your work

2 Answers

3 votes

Answer:


\large\boxed{(3x-2)-(-5x+7)=8x-9}

Explanation:


(3x-2)-(-5x+7)\\\\=3x-2-(-5x)-7\\\\=3x-2+5x-7\qquad\text{combine like terms}\\\\=(3x+5x)+(-2-7)\\\\=8x-9

User Arpit Agarwal
by
5.0k points
3 votes

3x-2

-(-5x+7)

☝️this is your equation

distribute your subtraction sign to -5x+7 and you get

3x-2

+5x-7

add everything together and you end up with

8x-9

User Huacanacha
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.